2020
DOI: 10.2147/oas.s198038
|View full text |Cite
|
Sign up to set email alerts
|

<p>Optimal Management of Post-Laryngectomy Pharyngo-Cutaneous Fistula</p>

Abstract: The pharyngocutaneous fistula (PCF) is one of the most common post-operative complications in patients undergoing laryngectomy. Up till now, there is no universally accepted algorithm for managing of PCFs and several treatment modalities are used for wound healing. The English language literature was searched using PUBMED databases with the keywords "laryngectomy", "pharyngocutaneous", "fistula", "treatment", and "management" from January 1, 1999 to June 1, 2019; we selected 35 studies according to inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…22 In a recent systematic review, primary conservative therapy was found to have a pooled effectiveness of 56 to 90% in patients with head and neck fistulae. 23 As it has long been known that many fistulas will close with appropriate wound care, and foundations of conservative fistula management are well established, it is advisable to avoid intraoral feedings with concurrent enteral or parenteral nutrition, antibacterial therapy, routine debridement, and pressure dressings or packing. 24 Minimizing contamination of the surrounding tissues is paramount to optimal healing of fistula tracts and, as such, patients should remain strictly nothing per os for the duration of therapy.…”
Section: Conservative Managementmentioning
confidence: 99%
See 4 more Smart Citations
“…22 In a recent systematic review, primary conservative therapy was found to have a pooled effectiveness of 56 to 90% in patients with head and neck fistulae. 23 As it has long been known that many fistulas will close with appropriate wound care, and foundations of conservative fistula management are well established, it is advisable to avoid intraoral feedings with concurrent enteral or parenteral nutrition, antibacterial therapy, routine debridement, and pressure dressings or packing. 24 Minimizing contamination of the surrounding tissues is paramount to optimal healing of fistula tracts and, as such, patients should remain strictly nothing per os for the duration of therapy.…”
Section: Conservative Managementmentioning
confidence: 99%
“…Optimization of nutritional status remains critical to adequate wound healing and, as such, enteral feedings via nasogastric tube-or if contraindications to enteral feedings exist, parenteral nutrition-are an essential component of fistula management and monitoring of albumin and prealbumin levels is routinely recommended. 23 In an effort to reduce drainage of secretions into the fistula tract, some authors also recommend placement of a salivary bypass tube. 25 Similar to nutritional status, the patient's volume status should be closely monitored in the healing period, with maintenance of euvolemic through intravenous fluids or transfusions as needed as fistula have been shown to cause fluid losses similar to those of a large burn.…”
Section: Conservative Managementmentioning
confidence: 99%
See 3 more Smart Citations